The Use of Motivational Strategies by EFL Primary School Teachers - Sitorus, Herlina (JET ADI BUANA, 2016)
This study aimed at examining motivational strategies utilized by two groups of EFL primary school teachers, experienced and novice teachers. A questionnaire developed by Cheng and DÃ¶rnyei (2007), was used in this study. Two research questions were posed: the first was to find which motivational strategies used by teachers in the classroom and the second was to explore which motivational strategies were most and least frequently used by experienced and novice teachers. The participants were nine EFL teachers, teaching English in a private primary school in Indonesia. Data was collected through questionnaires and interview. The results indicated some differences and similarity that both groups used. The experienced ones used more varied strategies from the novice ones.